Capitals of Punk DC, Paris, and Circulation in the Urban Underground - Sonnichsen, Tyler; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Capitals of Punk tells the story of Franco-American circulation of punk music, politics, and culture, focusing on the legendary Washington, DC hardcore punk scene and its less-heralded counterpart in Paris. This book tells the story of how the underground music scenes of two major world cities have influenced one another over the past fifty years. This book compiles exclusive accounts across multiple eras from a long list of iconic punk musicians, promoters, writers, and fans on both sides of the Atlantic. Through understanding how and why punk culture circulated, it tells a greater story of (sub)urban blight, the nature of counterculture, and the street-level dynamics of that centuries-old relationship between France and the United States.
Chapter 1: Introduction: A Tale of Two Cities and Scenes -- Chapter 2: DC and Paris: Capitals of Punk -- Chapter 3: A Brief History of Franco-American Circulation in the Twentieth Century -- Chapter 4: Washington Geography and the Birth of HarDCore, 1979-1983 -- Chapter 5: Hardcore Vient à Paris, 1983-1987 -- Chapter 6: This Is Not a Fugazi Book: HarDCore Comes of Age -- Chapter 7: Earthquakes Come Home: French Punks Visit DC -- Chapter 8: "We Were Fucking Tourists, in the End": Punk, Tourism, and Gentrification -- Chapter 9: Ian MacKaye Is Alive and Well and Living in DC:Concluding Thoughts.
Keywords: Human geography; Music; Sociology, Urban; Human Geography; Music; Urban Sociology